On the Inverse Problem for Generalized One-Sided Concept Lattices - Pócs, Jozef; Pócsová, Jana (Informatica, 2014)
Generalized one-sided concept lattices represent a generalization of the classical concept lattices convenientfor analysis of object-attribute models with different types of attributes. Formally, to each objectattributemodel (represented by the notion of formal context) there is assigned a pair of concept-formingoperators. Fixed points of these operators form a hierarchical structure consisting of extent-intent pairs.From the algebraic point of view this structure forms a complete lattice, called the generalized one-sidedconcept lattice. In this paper we deal with the inverse problem for generalized one-sided concept lattices.For a given generalized one-sided concept lattice we describe an algorithm for finding the correspondingformal context.